PENGARUH PERBEDAAN CHEMICAL PENETRATION ENHANCER PADA PENETRASI TRANSDERMAL PATCH PROMETAZIN HCL - Dwi Nurahmanto (jurnal ilmiah manuntung sekolah tinggi ilmu kesehatan samarinda, 2016)
This research aims is to create a promethazine HCl patch transdermal drug delivery systems with the most excellent penetration. Transdermal drug delivery can be efficiently used for the active agents which undergo rapid first pass metabolism and oral absorption is often disrupted by nausea and vomiting, hence the transdermal patches of promethazine HCl were prepared by using different penetration enhancers, propylene glycol, oleic acid and isopropyl alcohol. The prepared formulations were evaluated for thickness, weight variation, moisture content, drug content, morphology, and in vitro permeation studies. The patch morphology studies were performed by Scanning Electron Microscopy (SEM). The amount of promethazine HCl transfered by propylene glycol 25.77 ± 3.0396 ug, isopropil alcohol 25.758 ± 2.9022 ug and oleic acid 25.017 ± 8.1300 ug. The penetration of promethazine HCl patch with oleic acid enhancer, produce the highest penetration than isopropil alcohol and propylene glycol. there was no difference in penetration using propylene glycol and isopropyl alcohol. Oleic acid is the best enhancer for preparations patch containing promethazine HCl although the amount of promethazine HCl contained is the least. The whole formulations comply with the patch dosage requirements